Mathematical modeling and numerical simulations of javelin throw - Maryniak, J.; Ladyzynska-Kozdras, E.; Golinska, E. (Human Movement, 2009)
A physical model of the human-javelin system has been developed together with a mathematical model of javelin flight including its transverse elastic vibrations. Three kinds of parametric identifications were distinguished: geometrical, mass and aerodynamic. Numerical calculations were made for different initial velocities and throwing angles. The results obtained have been presented graphically.